Orthogeriatric Care in Hip Fracture Patients: Outcomes from Two Randomized Controlled Trials - Noor-Ul-Ain Malik Sohail, Attiq ur Rehman, Muhammad Rizwan Khan Lodhi, Sajjad Ali, Muhammed Salman Khalil Uppal, Muhammad Waseem (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Hip fractures in older adults often lead to significant functional decline and increased dependency.This study evaluates the impact of comprehensive geriatric care (CGC) compared to standardorthopedic care (OC) on functional outcomes in hip fracture patients.